Discovery of a new stonefly genus with three new species from mid-Cretaceous Burmese amber (Plecoptera: Perlidae) - Chen, Zhi-Teng; Wang, Bo; Du, Yu-Zhou (Zootaxa, 2018)
A new fossil stonefly genus of the subfamily Acroneuriinae Klapálek, 1914 (Plecoptera: Perlidae), Largusoperla gen. nov. is reported based on three well-preserved specimens in mid-Cretaceous amber from northern Myanmar. Three new species of this new genus, L. acus sp. nov, L. flata sp. nov and L. arcus sp. nov. are described and illustrated. This is the first report of stonefly specimens from mid-Cretaceous Burmese amber. The taxonomic placement of the new genus is discussed.